Understanding the Role of Technology in Islamic Religious Education - Unik Hanifah Salsabila; Inda Laela Wahdah; Ahmad Syafiq Muharrom; Adinda Dika Insani; Siti Sa'diyah Putri Widiastuty (Tarbiyah Departement collaboration with AMCA, 2023)
This study intends to determine the function of educational technology in the learning paradigm of Islamic religious education in the modern period, particularly after the COVID-19 epidemic, which altered the educational hierarchy in Indonesia. This study uses a qualitative research approach with a library research approach. Data collection by identifying various articles, journals, books or other sources. The analysis technique uses structured qualitative analysis. The findings of this study will demonstrate that educational technology plays a crucial role in Islamic religious education, particularly for high school and college students, particularly in each student's religious life and the afterlife. Technology and education are both readily available at a variety of educational levels. In education, the relationship between education and educational technology occurs naturally. The distribution of instructional materials requires the use of technology to facilitate the learning process. In light of this, we will investigate the role of educational technology in Islamic religious education in this article's discussion. Normalizing the school system in Indonesia is one of these measures after Indonesia adopts a new ordinary policy.